The Role of English Pop Songs in Listening Skills Learning among Maritime Students - Yoana G. P. Lengari (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Akademi Maritim Nusantara Cilacap, 2024)
Effective listening is important for seafarers, but often overlooked in English language teaching. Listening skills are often overshadowed by grammar and writing instruction. To address this problem, researchers and educators are exploring innovative approach in improving listening comprehension, including the use of pop songs as a potential tool to help the students. This study aims to investigate engineering students’ perceptions towards the use of English pop songs in listening exercises and assessing the effectiveness of this approach in improving their listening comprehensions, especially in Maritime English subject. This study employs a descriptive qualitative approach and using two instruments to gather the data. The first one is a questionnaire to gather data on students’ perceptions, attitudes, and experiences related to using English pop songs for listening improvement. Focus group discussion is conducted to dig deeper into students’ perspective and gather qualitative data. The respondents of the study are twenty students from the fourth-semester in Marine Engineering Program at Akademi Maritim Nusantara Cilacap. The questionnaire revealed positive perceptions toward the use of pop songs for vocabulary enrichment, pronunciation practice, and overall listening comprehension. However, the respondents also identified challenges related to different English accents that they hear in the songs. Moreover, focus group discussion emphasized the enjoyment and the motivation the respondents experience in their lessons compare to traditional listening materials. To conclude this study, the finding suggests a positive perception from the students that the use of English pop songs help them improve their listening skills.